Limosilactobacillus reuteri FN041 prevents atopic dermatitis in pup mice by remodeling the ileal microbiota and regulating gene expression in Peyer’s patches after vertical transmission - Zhou, Jingbo; Xu, Gaoshun; Li, Xinyue; Tu, Huayu; Li, Haoyu; Chang, Hong; Chen, Jie; Yu, Renqiang; Qi, Ce; Sun, Jin (Frontiers in Nutrition, 2022)
Objectives: Limosilactobacillus reuteri FN041 is a potential probiotic bacterium isolated from breast milk in traditional farming and pastoral areas of China. The purpose of this study was to investigate the optimal intervention mode and potential mechanism of FN041 to prevent atopic dermatitis (AD) in mice. Methods: In intervention mode I, FN041 was supplemented to dams during the late trimester and lactation and pups after weaning; in intervention mode II, FN041 was supplemented after pups were weaned. AD was induced in pups with MC903 plus ovalbumin on the ear after weaning. Results: The effect of intervention mode I in preventing AD was significantly better than that of intervention mode II. Compared with the model group, the inflammatory response of the pup's ears, the proportion of spleen regulatory T cells and the plasma IgE were significantly decreased in mice in intervention mode I. Furthermore, the intestinal mucosal barrier was enhanced, and the Shannon index of the ileal microbiota was significantly increased. The microbiota structure deviated from the AD controls and shifted toward the healthy controls according to the PCoA of unweighted UniFrac. The relative abundances of Limosilactobacillus, Faecalibacterium, Bifidobacterium and Akkermansia in the ileum were significantly increased compared to the AD group. Based on RNA-seq analysis of pups' Peyer's patches (PPs), FN041 inhibits autoimmune pathways such as asthma and systemic lupus erythematosus and activates retinol metabolism and PPAR signaling pathways to reduce inflammatory responses. Intervention mode II also significantly reduced AD severity score, but the reduction was approximately 67% of that of intervention mode I. This may be related to its ineffective remodeling of the ileal microbiota. Conclusions: Prenatal and postnatal administration of FN041 is an effective way to prevent AD in offspring, and its mechanism is related to remodeling of ileal microbiota and PPs immune response.